Ettringite-based binder from ladle slag and gypsum – The effect of citric acid on fresh and hardened state properties. (September 2019) - Nguyen, Hoang; Kinnunen, Paivo; Gijbels, Katrijn; Carvelli, Valter; Sreenivasan, Harisankar; Kantola, Anu M.; Telkki, Ville-Veikko; Schroeyers, Wouter; Illikainen, Mirja
Abstract: The retardant effects of citric acid on the properties of ettringite binders are not yet fully understood. This investigation provides insights into the effects of citric acid on both the fresh and hardened state properties of the binder produced from the hydration between ladle slag and gypsum (LSG). The results revealed that LSG's initial setting time could be controlled via different citric acid contents and could range from 20 min to 2 h. Citric acid is effective at relatively high dosages; in its absence, ettringite formed almost immediately directly following exposure to water. The presence of citric acid alters the hydration reactions in LSG. AFm was found to be one of main hydration products; citric acid promoted the conversion from ettringite to monosulfate, detected by using solid-state 27 Al magic-angle spinning nuclear magnetic resonance spectroscopy. In addition, citric acid increased the compressive strength of LSG mortars by up to 45%.